The Effect of ERM, Disclosure of CSR and Profitability on the Company Value with Company Reputation as A Moderating Variable - Suharti Suharti; Regina Jansen Arsjah (Institut Bisnis dan Teknologi Pelita Indonesia, 2026)
This study analyzes the impact of ERM, CSR disclosure and profitability on company value with the moderating variable company reputation in manufacturing zones listed on the Indonesian money market in the 2015-2020 research period. This study uses inferior data. The sampling technique in this study uses probability sampling procedures with a saturated sampling method. The number of illustrations obtained was 94 industries. The procedure for analyzing this research uses descriptive analysis and several types of assessment using the SmartPLS application. From the test results, it was concluded that only ERM and profitability (ROA) had a positive influence on company value. On the other hand, CSR disclosure does not affect company value. After that, the good name of the industry cannot strengthen the impact of ERM, CSR disclosure and ROA on company value